Understanding the relationship between rheological characteristics of pulsed electric fields treated chitosan-zein-poly(vinyl alcohol)-polyethylene glycol composite dispersions and the structure-function of their resulting thin-films. (April 2021) - Giteru, Stephen G.; Ali, Azam; Oey, Indrawati
Abstract: For the first time, this article elucidates how the rheological behavior of pulsed electric fields (PEF) treated chitosan-zein-poly (vinyl alcohol)-polyethylene glycol composite affects the physicochemical properties of the resulting biodegradable films. The dispersion was subjected to varying specific energy ( Q P ) (60–400 kJ/kg) or electric field strength ( E P ) (0.8–3.4 kV/cm) before being developed into biodegradable films. Increasing the intensity of both Q P and E P modified the dispersions' consistency, which became dominated by high-density molecular entanglements, leading to higher viscosity, Z-average diameter, and polydispersity index. The attenuated total reflectance-Fourier transform infrared spectroscopy results confirmed that PEF-treatment promoted extended chain conformation and exposed multiple reactive sites that facilitated intermolecular entanglements and bioconjugation between the biopolymers. Exposing the dispersions to QP > 160 kJ/kg (delivered at 3.4 kV/cm) or E P of 0.8–3.4 kV/cm ( Q P 585–633 kJ/kg) resulted in higher thermal stability as observed using TGA. Microstructural properties examined by X-ray diffraction and scanning electron microscopy showed clear interaction between the biomacromolecules at PEF intensities of Q P 150–400 kJ/kg and E P 1.6–3.4 kV/cm through complex coacervation. These interactions resulted in regular, compact, and crystalline formations of the cast films. Nevertheless, films with high stability in a wet environment can be developed by subjecting the dispersions to Q P of ~60 kJ/kg and EP of 0.8 kV/cm. The findings demonstrated how the combined mechanisms of PEF-induced microstructural modification of composite colloidal dispersions and protein-polysaccharide phase separation could be used to tailor biodegradable films. Graphical abstract: Image 1 Highlights: Pulsed electric fields (PEF) processing can modify protein-polysaccharide interactions. Alterations in the colloidal dispersions during PEF were transferable to the cast films. Bioconjugation promoted complex coacervation between biomacromolecules. PEF is a potential tool for product design in restructuring biopolymeric materials.